Analysis of the Effectiveness of Flash Floods Disaster Mitigation in Java Island - Alfa Nugraha Pradana; Annissa Nur Fitria Fathina; Anwar Fitrianto; Bagus Sartono; Sachnaz Desta Oktarina (Sriwijaya Journal of Environment, 2022)
Flash flood is one of the natural disasters that currently happens a lot in Indonesia. Java Island is one of the largest archipelagoes in Indonesia and has the highest incidence of flash floods. Several efforts were conducted to anticipate and mitigate flash floods in Java Island, including an early warning system, preparing safety equipment, building evacuation route signs, and monitoring watersheds. Through the dataset of Village Potential 2018, this study aims to explore the effectiveness of flash flood mitigation in Java Island using the R programming language. The stages of research carried out in this study are data preprocessing, including selecting, recoding the variables, exploratory univariate, bivariate, and multivariate data analysis. The results showed that the fatalities of flash floods often occurred in areas with plains surface, especially in West Java and East Java, followed by the topography of Central Java on the hills and the valleys in Banten. In addition, the most effective disaster mitigation established in Java Island is safety equipment and the construction of evacuation route signs compared to other disaster anticipation efforts.